Solar-Based Fuzzy Intelligent Water Sprinkle System - Muhida, Riza; E. Salami, Momoh Jimoh; Astuti, Winda; Bt Ahmad Kasim, Nurul Amalina; Rahayu, Nani (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2011)
A solar-based intelligent water sprinkler system project that has been developed to ensure the effectiveness in watering the plant is improved by making the system automated. The control system consists of an electrical capacitance soil moisture sensor installed into the ground which is interfaced to a controller unit of Motorola 68HC11 Handy board microcontroller. The microcontroller was programmed based on the decision rules made using fuzzy logic approach on when to water the lawn. The whole system is powered up by the solar energy which is then interfaced to a particular type of irrigation timer for plant fertilizing schedule and rain detector through a simple design of rain dual-collector tipping bucket. The controller unit automatically disrupted voltage signals sent to the control valves whenever irrigation was not needed. Using this system we combined the logic implementation in the area of irrigation and weather sensing equipment, and more efficient water delivery can be made possible.Â